Pengaruh Green Innovation dan Green Invesment terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi Pada Perusahaan Yang Terdaftar di Indeks IDX LQ45 Low Carbon Leaders - Rahmawati, Hanif; Sartika, Farahiyah (Universitas Negeri Padang, 2025)
This study aims to examine the effect of green innovation and green investment on firm value, as well as the role of company size as a moderating variable in companies listed on the IDX LQ45 Low Carbon Leaders Index for the period 2022-2024. This study uses a quantitative approach with purposive sampling method and obtained 14 companies as samples. Secondary data is obtained from annual reports and corporate sustainability. Data analysis techniques include multiple linear regression to test the direct effect of independent variables on firm value, as well as Moderated Regression Analysis (MRA) to test the role of company size as a moderating variable. The results showed that green innovation has a positive and significant effect on firm value. However, green investment has no significant effect on firm value. In addition, company size is unable to moderate the effect of green innovation and green investment on firm value. These results provide insight for companies to focus on green innovation as a strategy to improve competitiveness and reputation in the market. This study also has implications for investors and regulators to consider sustainability aspects in decision making.